Design of PID tuning rule using optimization method - Abdallah Awouda, Ala Eldin (Praise Worthy Prize, 2010)

(untitled)
This paper discusses an approach to tune the PID controller parameters using the optimization method. The method involves analytically calculating the gain of the controller (Kc), integral time (Ti) and the derivative time (Td) for PID controlled systems whose process is modeled in first order lag plus time delay (FOLPD) form. A mat lab program is used to find the optimum value of the PID controller parameters which can achieve most of the systems requirements such as reducing the overshoot, maintain a high system response, achieve a good load disturbances rejection and maintain robustness. The objective function is selected so as to minimize the integral of Time Absolute Error UAE) performance index. A comparison between the proposed tuning rules and the traditional tuning rules is done through the Matlab software to show the fficiency of the new tuning rule.